2020
DOI: 10.1002/cncr.33238
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between genitourinary cancer patients' and clinicians' characterization of the Eastern Cooperative Oncology Group performance status

Abstract: BackgroundPatient‐reported outcomes have been used to assess treatment effectiveness and actively engage patients in their disease management. This study was designed to describe the patient‐reported performance status (PS) and the provider‐reported PS.MethodsPatients with metastatic genitourinary cancers were recruited from a single cancer center before the initiation of a new line of treatment. PS (Eastern Cooperative Oncology Group [ECOG]), quality of life (Functional Assessment of Chronic Illness Therapy–G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…The findings described by Bergerot et al 8 for discrepancies in provider‐ and patient‐rated ECOG scores could be due to a wide variety of contributory factors. In addition to physical status, providers must take care to consider a broader range of psychosocial factors such as mental health, social well‐being, and education level when evaluating the PS of a patient with cancer.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…The findings described by Bergerot et al 8 for discrepancies in provider‐ and patient‐rated ECOG scores could be due to a wide variety of contributory factors. In addition to physical status, providers must take care to consider a broader range of psychosocial factors such as mental health, social well‐being, and education level when evaluating the PS of a patient with cancer.…”
mentioning
confidence: 86%
“…Emerging research calls this practice into question by demonstrating that provider ratings of PS may be discordant from patient ratings 6,7 . Bergerot et al 8 took a critical look at provider and patient reports of ECOG PS in patients with metastatic genitourinary cancer. They found that providers were more likely than patients to give an ECOG score of 0 (92.4% vs 64.1%; P = .001).…”
mentioning
confidence: 99%
See 3 more Smart Citations